Synthetic Biology: Science of the inthinkable - Zahid, Zuhair R. (Journal of the Faculty of Medicine Baghdad, 2012)
During the 3rd BBIC (Biosafety and Biosecurity international conference), in Amman, 13-15 September 2011, I witnessed the most astonishing and elegant lecture by the pioneer in this field Dr. Andrew Hessel (1).